Decision making for government-funded HPV vaccination programs in China: a multiple streams framework-based analysis - Shu-jun LIU; You-lin QIAO; Cai-hong ZHOU (Editorial Office of Chinese Journal of Public Health, 2023)
Persistent infection of human papillomavirus (HPV) can cause a variety of diseases including cervical cancer, which affects human health and leads to a huge socio-economic burden. Although it has shown that HPV vaccines could effectively prevent HPV infection and reduce cervical cancer incidence, China hasn't introduced HPV vaccination into the national immunization program. The multiple streams framework proposed by Kindon is an essential theoretical tool for analyzing public policy agendas and is suitable for analyzing decision-making processes of immunization programs. In this study, we adopted multiple streams framework to assess main influencing factors of introducing HPV vaccination into the immunization programs by examining the problem stream, policy stream, politics stream, the policy spillover effect of pilot cities, and the role of policy entrepreneurs. And we also give some suggestions to promote the inclusion of HPV vaccines in the immunization programs at regional and national levels, and finally achieve the purpose of 'eliminating cervical cancer'.